Police crime in 1947 in the coverage of the Ukrainian SSR state security agencies - O. N. Yarmysh; V. A. Grechenko (Law and Safety)
One of the least researched issues in historical and legal science, such as crime in one of the main law enforcement agencies of police, which operated on the territory of the Ukrainian SSR, has been covered. Instead of counteracting, some police officers organized crimes and participated in them personally. The involvement of police officers in various criminal and official crimes has been revealed: treason during the Soviet-German war, robbery, bribery, extortion, assistance to criminals, official negligence. Materials collected by the employees of the Ministry of State Security regarding some negative aspects of the police officers activities during 1947 testify to significant abuses and violations of the law. It has been established that a certain part of the policemen were traitors during the war, worked with the occupation authorities and took part in repressions against members of the Resistance movement and ordinary people. This problem was acute at that time, because only 2 years had passed since the end of the war, and the state security authorities continued to work on identifying and detaining these persons, who were also among the police officers.